OLIGOCENE CALCAREOUS PLANKTON FROM THE KRONOTSKII PENINSULA, EASTERN KAMCHATKA - Stupin S.I.; Shcherbinina E.A.; Vitukhin D.I.; Serova M.Ya.; Tsukanov N.V.; Pachkalov A.S. (My University, 1998)
Planktonic foraminifers and calcareous nannoplankton were first recorded along with benthic foraminifers in the Upper Paleogene section of the Kronotskii Peninsula, eastern Kamchatka. The fauna permits the assignment of the enclosing sediments to the Globigerina ampliapertura Zone of the foraminifer zonation of Bolli and Saunders, (1985) and to the nannoplankton zones CP17-CP18 of the Lower Oligocene. The sporadic occurrence of calcareous plankton in Oligocene sediments of high latitudes was most likely a consequence of the World Ocean level rise and relative climatic warming.
Keywords: Oligocene; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен